Analysis of the Impact of Government Policy, Technological Innovation, and Availability of Business Capital on the Growth of Small and Medium Enterprises in Indonesia - Afif Syarifudin Yahya; Fikri, Maiza; Judijanto, Loso; Utami, Eva Yuniarti; Iskandar, Deni (Westscience Press, 2024)
This research studies the complex relationships between government policies, technological innovation, availability of venture capital, and the growth of Small and Medium Enterprises (SMEs) in Indonesia. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS), this research analyses data from a sample of 130 SMEs across different industries and regions. The measurement model assessment confirmed the reliability and validity of the constructs, while the structural model analysis revealed significant positive relationships between government policy effectiveness, technological innovation, venture capital availability, and SME growth. The robustness of the findings was confirmed through bootstrapping, and the model fit index validated the adequacy of the estimated model. The R-squared values indicate the ability of the model to explain most of the variance in SME growth. Hypothesis testing further corroborated the significant impact of Availability of Venture Capital, Government Policies, and Technological Innovation on SME growth. The implications of these findings extend to policymakers, business owners, and stakeholders, guiding the formulation of strategies that foster an enabling environment for SMEs in Indonesia.